Awareness of gender-sensitive expressions in the print media - Mohamed Ali, Haja Mohideen (2010)
Most contemporary and sensitive English language users, especially women and those who are careful not be misunderstood as insensitive language users do not consider „man‟ to be synonymous with „people‟. Therefore users of the English language, and for that matter any language, have to be mindful about the ways gender is expressed in discourse. This paper will deal with the print and online editions of the Malaysian daily newspaper The Star for the month of December, 2009. The study is primarily focused on nouns which are gendered in a way regarded as inappropriate because the noun refers to the wrong gender, or it is expressed in such a manner that it excludes one of the two genders, when both should be rightly included. The paper will confine itself to local (Malaysian) news items. It will elaborate on both the proper use of non-sexist language and that which is deemed sexist. The findings are expected to bring about greater awareness of gender-sensitive usage and lead to their appropriate use in the print media.